Best friend to husband? - Heaton, Louisa (Cotswold docs, 2025)
GP Lorna has spent years healing from a divorce and the end of her fertility journey by throwing herself into her work at Clearbrook Medical Practice. But when Oliver-her onetime best friend and secret crush-takes a job as a doctor at her surgery, life suddenly becomes more complicated! After the breakdown of his difficult marriage, Oliver isn't looking for romance, either. Yet old feelings soon begin to resurge. Can they risk their friendship in the hope of something more?